IMPLEMENTATION OF THE EOQ (ECONOMIC ORDER QUANTITY) METHOD IN INVENTORY CONTROL AT BENNY'S WHOLESALE STORE - Maryanto; Tiara Lilis Surya; Cyntia Carolina; Haikal Kurniawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Unplanned inventory management can lead to excess stock and increased inventory costs. Based on 2024 data, Grosir Benny experienced a condition where incoming goods exceeded outgoing goods, indicating inefficient inventory control. This study aims to analyze inventory management before the implementation of the Economic Order Quantity (EOQ) method and to evaluate the effectiveness of EOQ in determining optimal order quantities. This research employs a quantitative descriptive method with instant noodle inventory as the object of study. The results show that the EOQ method produces an optimal order quantity of 24 cartons per order with 46 orders per year. The calculated safety stock is 42 cartons, and the reorder point is 49 cartons. The implementation of the EOQ method is considered more effective than the previous system, as it aligns order quantities with sales levels, reduces the risk of overstocking, and improves inventory cost efficiency.